A Review of Absolute Radiometry Calibration Method for Satellite Multispectral Camera while in Orbit - Sartika Salaswati; Saputro, Adhi Harmoko; Hasbi, Wahyudi (Indonesian Journal of Aerospace, 2024)
Multispectral cameras on satellites are a type of camera that is widely used in satellite remote sensing and has wide applications. Therefore, it is necessary to carry out absolute radiometric calibration to maintain the accuracy of radiometric information in satellite camera images. There are several types of absolute radiometric calibration, including onboard, Rayleigh, vicarious, and cross-calibration. These methods have strengths and weaknesses. Therefore, it is necessary to conduct a literature review to find out which calibration method is appropriate for certain conditions. Based on a literature review, all methods can be used and adapted to the conditions of the satellite. The onboard calibration method is suitable for satellites equipped with calibration instruments. The Rayleigh calibration method is suitable for large FOV cameras with visual wavelengths. The vicarious calibration method is suitable for satellites from countries close to standardized calibration sites. Meanwhile, the cross-calibration method is suitable for satellites cameras that have specifications and conditions close to the reference camera. Therefore, these calibration methods can be carried out together to complement each method.